The whisper - Starmer, Aaron, 1976- (New York : Farrar Straus Giroux, 2015)
Twelve-year-old Alistair continues his quest to find his missing friend, Fiona, in Aquavania, a world where wishes can nearly come true, but he learns that the Whisper, once a boy named Charlie from his own world, has plans for Alistair and has used Fiona to try to get to him.
Keywords: Friendship -- Juvenile fiction; Fantasy; Friendship -- Fiction; Fantasy; Fantasy fiction